Influence of sealing materials on the oxygen permeation fluxes of some typical oxygen ion conducting ceramic membranes - Chen, Y.; Qian, B.; Hao, Y.; Liu, Shaomin; Tade, Moses; Shao, Zongping (Elsevier BV, 2014)
In this study, the influences of sealing materials on the oxygen permeation fluxes of three typical dense oxygen permeating membranes, including PrBaCo2O5+δ (PBC), Ba0.5Sr0.5Co0.8Fe0.2O3−δ (BSCF5582) and Ce0.8Sm0.2O1.9 (SDC), with high electronic conductivity, moderate electronic conductivity and dominant oxygen-ion conductivity, respectively, are systematically investigated. Silver and insulating ceramic are used as two different sealants. The effects of external short circuit for electronic conduction by applying silver sealant and potential contamination effect of ceramic sealant on membranes were taken into major consideration. PBC membranes with either silver or ceramic as sealant showed comparable oxygen permeation flues during the test. Similar conclusions were also obtained based on BSCF5582 membranes. As for SDC membrane, significant promotion of the permeation flux by applying silver sealant was clearly demonstrated. Explanations for these performance changes are proposed. The findings from this study may provide valuable insight to explain the discrepancy of oxygen permeation fluxes of some membranes as reported by different research groups in the literature.